Heavyweight limits for men - Curby, D. (International Journal of Wrestling Science, 2023)
Beginning with the 1985 world championships, FILA instituted a maximum weight of 130 kg (286 lbs.) for the highest weight class. In past days the heavyweight division was also called "unlimited," since there were no upper limits. As a matter of fact, in the first modern Olympic Games, there was only one class for everyone. Throughout the 20th century there was a gradual increase in the number of weight classes used in the Games. It can be a bit confusing since some of the early Games did not always have competition in both Greco-Roman and Freestyle. Sometimes, even when there were both styles, they had different weight classes. The number of classes grew, as well as the minimum weight used for the heavyweight class.